Smarthome-mobile app development in flutter for smart home management - Culanda, Vadson Guilherme Avelino (2021)
The Internet of Things has accelerated the availability of solutions for smart homes, o ering an increasingly varied range of products and smart home applications that aim to simplify daily tasks and increase user comfort. However, the available systems are often excessively complex from the user's perspective, making their use unintuitive and unpredictable. Within the scope of this dissertation, an application for smart homes was developed based on the Flutter framework, which can interact with Altice labs' Smart Home device ecosystem. This document presents a comparison between the various existing smart home solutions, as well as an overview of the solution developed by Altice labs. The implementation of the proposed solution is detailed using code excerpts that illustrate the choices made in terms of design and functionality. Finally, the developed application is evaluated using a test process that veri es compliance with its requirements.